Hip arthroscope-assisted percutaneous reduction and fixation of displaced subcapital femoral neck fracture - Dajiang Du; Che Zheng; Mengxin Xue; Jiewei Chen; Yiyang Ma; Yun Gao; Changqing Zhang (Frontiers in Surgery)
Reduction quality is associated with fracture prognosis. Displaced subcapital femoral neck fracture has highest possibility of avascular necrosis of femoral head and non-union among the femoral neck fractures, which commonly necessitate revisions or hip replacement. This study introduces for the first time of using hip arthroscope to directly visualize and assist the reduction of displaced subcapital femoral neck fracture when closed reduction is unsatisfactory. Due to the minimally invasive advantage of arthroscopic assistance, radiation exposure or intraoperative bleeding can be reduced, open reduction is avoided so that the blood supply of femoral head can be preserved. Through direct visualization, the complete removal of hematoma and fracture debris can be achieved, which is not possible with closed reduction, and can potentially reduce the risk of non-union during bone healing.